Makers and takers: The economics of the Kalshi prediction market - Constantin Bürgi; Wanying Deng; Karl Whelan (University College Dublin, UCD School of Economics, 2025)
Since 2021, Kalshi has operated as the only federally licensed prediction market in the United States. Using transaction-level data on over 300,000 contracts, we provide the first systematic evidence on its pricing. Kalshi's contract prices are informative and improve in accuracy as markets approach closing, but they display a clear favorite-longshot bias: low-price contracts win far less often than required to break even, while high-price contracts win more often and yield small positive returns. We interpret these patterns with a simple framework that reflects Kalshi's quotedriven microstructure. Makers-relatively well-informed traders who post offers-seek positive expected returns but may be slightly over-optimistic, while Takers accept these offers. The model predicts distinct patterns of favorite-longshot bias for Makers and Takers, and the data confirm these predictions.
Keywords: G14; G23; G40; 330; Prediction Markets; Kalshi; Favorite-Longshot Bias; Market Microstructure; Bid-Ask Spreads